Improving the design of heart failure care from the perspective of frontline providers and administrators: A qualitative case study of a large, urban health system. (4th June 2020) - Marani, Husayn; Baranek, Hayley; Abrams, Howard; McDonald, Michael; Nguyen, Megan; Posada, Juan Duero; Ross, Heather; Schofield, Toni; Shaw, James; Bhatia, R Sacha
Background: Heart failure patients often present with frailty and/or multi-morbidity, complicating care and service delivery. The Chronic Care Model (CCM) is a useful framework for designing care for complex patients. It assumes responsibility of several actors, including frontline providers and health-care administrators, in creating conditions for optimal chronic care management. This qualitative case study examines perceptions of care among providers and administrators in a large, urban health system in Canada, and how the CCM might inform redesign of care to improve health system functioning. Methods: Sixteen semi-structured interviews were conducted between August 2014 and January 2016. Interpretive analysis was conducted to identify how informants perceive care among this population and the extent to which the design of heart failure care aligns with elements of the CCM. Results: Current care approaches could better align with CCM elements. Key changes to improve health system functioning for complex heart failure patients that align with the CCM include closing knowledge gaps, standardizing treatment, improving interdisciplinary communication and improving patient care pathways following hospital discharge. Conclusions: The CCM can be used to guide health system design and interventions for frail and multi-morbid heart failure patients. Addressing care- and service-delivery barriers has important clinical, administrative and economic implications.